Relation between self-awarness with basic hope and ways of coping with stress in the codependency women who are in a preliminary and advanced phase of therapy - Miklasiewicz, Marta (Studia Psychologica: Theoria et praxis, 2007)
The article presents some modern theoretical views of empirical studium on the functioning of co-dependency women in preliminary and advanced phase of therapy. The author contentrates on comparative analysis of functioning of co-dependency women in a preliminary and advanced stage of therapy in a context of three psychological variables: selfawareness, basic hope, and the ways of coping with stress.